ANALYSIS OF THE EFFECTIVENESS OF THE DEVELOPED METHODOLOGY FOR SETTING THE TYPE AND THE VOLUME OF GUARANTEES TO WORKERS FOR WORKING CONDITIONS - Aitkenova, G.T.; Yesbenbetova, Zh.Kh.; Abikenova, Sh. K.; Mukanov , D. B. (Academic Journal of Physical and Chemical Sciences, 2018)
The features of the current system for establishing guarantees for workers engaged in heavy work, work with harmful and (or) dangerous working conditions in the Republic of Kazakhstan are highlighted in the article. The necessity of providing guarantees to workers engaged in heavy work, work with harmful and (or) dangerous working conditions, not only taking into account the state of working conditions, but also the state of their health is grounded. In this regard, it is proposed to introduce the Methodology for establishing the type and scope of guarantees to workers engaged in heavy work, work with harmful and dangerous working conditions, depending on the degree of occupational risk. In this article, calculations are made to provide the type and scope of guarantees to employees employed in the enterprise for the production of soft roofing and waterproofing materials, depending on the degree of occupational risk in the new developed methodology. The analysis of the effectiveness of the implementation of the proposed methodology in comparison with the current mechanism and the list approach in providing guarantees to employees was carried out. The application of the proposed methodology has a positive effect on the regulation of labor relations between employers and employees and is recommended for use in domestic enterprises.